Association between mental well-being and sense of self-efficacy among faculties in Kathmandu University School of Medical Sciences: A cross-sectional study - Adhikari, Umesh; KC, Prajita; Shrestha, Rajan (Journal of Chitwan Medical College, 2026)
Introduction: Mental well-being is an increasing public health concern and is crucial for professionals working in high-stress environments, such as medical educators. Teaching in medical institutions presents unique challenges that can impact educators' mental well-being, potentially influencing their sense of self-efficacy. Despite existing research on self-efficacy and mental well-being in other professions, there have been limited studies exploring this relationship among medical faculty in Nepal. This study aimed to investigate the relationship between mental well-being and self-efficacy among faculty members at Kathmandu University School of Medical Sciences. Method: A cross-sectional study was conducted among 136 faculty members from different departments at Kathmandu University School of Medical Sciences from 10 May 2024 to 12 Mar 2025. The Warwick-Edinburgh Mental Well-Being Scale and the Faculty’s Sense of Self-Efficacy Scale were used to assess mental well-being and self-efficacy, respectively. SPSS version 25 was used for data analysis, and associations were examined using Fisher's exact test. Result: The majority of participants (74.3%) reported moderate mental well-being, while 14.7% experienced low, and 11.0% reported high well-being. Self-efficacy levels were predominantly sufficient (73.5%), while 26.5% had moderate self-efficacy. Mental well-being was significantly associated with self-efficacy (p=0.002), faculty designation (p=0.003), and self-efficacy with teaching experience (p=0.008). Faculty members with better mental health were more likely to have higher self-efficacy. Conclusion: The findings highlight a strong association between mental well-being and self-efficacy among medical faculty. Institutions should prioritize faculty mental health support and professional development programs.